The Paramount of Finance and National Development in Nigeria: Emphasis to Niger State Respective - Sulaiman Taiwo Hassan; Abalaka J. N; Ajiteru, S. A. R (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In order to reduce poverty and inequality and increase economic growth and productivity, the paper examines the importance of financial inclusion and national development in Nigeria, with a focus on Niger State. It does this by assisting individuals and businesses, particularly small and medium-sized enterprises (SMEs), in saving and investing, managing financial risks, and facilitating smooth consumption. This study identifies major supply-side and demand-side obstacles to financial inclusion as well as structural barriers, and it draws attention to Niger's relative behind other WAEMU nations in terms of youth and women's use of formal financial services. In order to assist the nation's development goal, it lays out major targets for Niger to harness the potential of increased financial inclusion. These include initiatives to address inadequate financial literacy, encourage digitization, and address informality.